BIAS GENDER DALAM PENANGANAN KASUS KEKERASAN TERHADAP PEREMPUAN SECARA LITIGATIF - Irwan Abdullah; Siti Ruhaini Dzuhayatin; Dyah Pitaloka (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2001)
The ongoing raise of violence against women shows that the issue refers to the problem of gender in its various dimensions. This is due to beliefs that the differences between men and women are laws of nature- have long been socially propagated. Aside from that, a strong culture of patriarchy has also been put women on powerless positions, as reflected in the handling of violence's cases through legal processes. This article is intended to analyse the problem through three major aspects. pirst, the law has a strong bias towards women as victims, in particular men as perpetrators of detrimental acts towards women. Second, bias in legal procedures which should be administered in the whole processes of litigation which occurs in a lot of violence's cases. Third, the attitude of law enforcements which stand opposed women both as the real victims and culturally as the subordinated classes.The article has showed that the performance of law-enforcement officials in dealing with violence against women has remained remarkably low.The main cause of such violence, may be due to the classic gender bias in the perspective of our legal system which has been reflected in the forms of the patriarchal order of society.